Idiopathic unilateral hyperhidrosis with Holmes-Adie syndrome - Kandi, B; Saral, Y; Belirgen, S; Öztürk, P (Japanese Dermatolgical Assoc, 2004)
Hyperhidrosis is a disease that is characterized by excessive sweating due to hyperactivation of eccrine sweat glands. It may be localized or generalized form. Holmes-Adie syndrome is an idiopathic disease with unilateral pupil dilatation and loss of deep tendon reflexes. We present a 37-year-old female patient diagnosed with unilateral hyperhidrosis coincident with Holmes-Adie syndrome because of this unusual presentation.
Keywords: idiopathic unilateral hyperhidrosis; Holmes-Adie syndrome